Imaging of reactive transport in fractured cement-based materials with X-ray CT. (November 2021) - Kuusela, P.; Pour-Ghaz, M.; Pini, R.; Voss, A.; Seppänen, A.
Abstract: The need to improve the understanding of the properties of cement-based materials calls for the development of tools for visualizing and quantifying chemical reactions and flows of fluids within them. In this paper, we report the results of an experimental study where a sample of fractured cement-paste was subjected to injection of fluids (krypton, CO 2 and water) and imaged simultaneously by X-ray computed tomography (CT). Initial porosity of the sample was estimated using a subtraction method based on CT scans taken initially and during krypton injection. The CT reconstructions were segmented to visualize crack patterns and fluid flow in three-dimensions and to quantify the evolution of porosity during the experiment. The results show that CT captures the formation of a carbonate phase in the sample during CO 2 injection, and the flow of water in the fractured media. We quantify the reduction of porosity resulting from the carbonation reaction. We observe that the newly formed carbonated layer impedes water flow and, locally, can lead to crack healing. The results demonstrate the ability of CT to image reactive transport in cement-based materials, and support the feasibility of this imaging tool for their characterization.